Exploring Undergraduate Students' Mental Well-Being, Mental Health Seeking Attitude, and the Impact of Socioeconomic Status: A Cross-Sectional Study from Malaysia - Abdul Rahman M. Fata Nahas; Nuraishah Omar; Ahmed M.Y. Osman; Nor Hidayah Mohd Taufek (Wolters Kluwer Medknow Publications, 2024)
Introduction: The future of our healthcare services highly depends on the current generation of health science students since they are the ones who will work in the healthcare setting. Ensuring their mental well-being is an utmost priority so that they can offer top-tier quality care and services to people in need. This study aimed to explore the prevalence of mental well-being and mental help-seeking attitude among undergraduate sciences students and the impact of socioeconomic status toward both variables. Materials and Methods: A cross-sectional study was conducted among students (N = 364) from six sciences schools at International Islamic University Malaysia via an online survey, which contained three main parts; socioeconomic status, mental well-being assessment using the Warwick-Edinburgh Mental Well-being Scale (WEMWBS), and assessment of mental help-seeking attitude using the General Mental Help-Seeking Attitude Scale (MHSAS). Data were analysed using SPSS, version 29.0. Results: Only 7.1% of the students have positive mental well-being, while 44.8% scored positive mental help-seeking attitude. There were no significant differences (P > 0.05) in students' mental well-being and any of SES components. There was a significant association between students' year of study and mental help-seeking attitude (P = 0.029), in addition, WEMWBS and MHSAS scores showed a positive correlation (P < 0.01). Conclusion: Future studies are essential to find out the contributing factors, prevention, and intervention that can be done to help the student in need.